Republic of Zambia Diagnostic Review of Consumer Protection and Financial Literacy : Volume 1. Key Findings and Recommendations - World Bank (World Bank, Washington, DC, 2017)
The Diagnostic Review of Consumer Protection and Financial Literacy in Zambia was conducted at the request of the Bank of Zambia (BoZ) and covered: i) banking; ii) non-bank financial institutions; iii) insurance; iv) pensions; and v) securities. The objectives of the Review were to compare the existing legal and regulatory framework, institutional arrangements, and market practices to good practices and provide recommendations to enhance financial consumer protection and financial literacy in Zambia. The Review consists of two Volumes. Volume I summarizes the key findings and recommendations and Volume II presents a detailed assessment of each of the covered sectors compared to the Good Practices. The key findings and recommendations presented in Volume I cover six areas: i) legal and regulatory framework; ii) institutional arrangements; iii) consumer disclosure; iv) business practices; v) dispute resolution mechanisms; and vi) financial education.